2003
DOI: 10.1002/adma.200301641
|View full text |Cite
|
Sign up to set email alerts
|

Oxide‐Assisted Growth of Semiconducting Nanowires

Abstract: In this contribution, we outline oxide‐assisted growth (OAG) (distinct from the conventional metal‐catalytic vapor–liquid–solid (VLS) process) for the growth of nanostructured materials. This synthesis technique, in which oxides instead of metals play an important role in inducing the nucleation and growth of nanowires, is capable of producing large quantities of high‐purity silicon nanowires with a preferential growth direction, uniform size, and long length, without the need for a metal catalyst. The OAG 1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
462
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(474 citation statements)
references
References 40 publications
7
462
0
5
Order By: Relevance
“…12,26,27 Experiments showed that SiNWs can be obtained by thermal evaporation or laser ablation of Si powder mixed with SiO 2 or SiO, 12,26,27 but there is no SiNWs growth from pure SiO 2 materials. 12 Reber et al 28 demonstrated that SiO units assemble to form bigger clusters, with silicon rich agglomerations at the center and oxygen rich structures at the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…12,26,27 Experiments showed that SiNWs can be obtained by thermal evaporation or laser ablation of Si powder mixed with SiO 2 or SiO, 12,26,27 but there is no SiNWs growth from pure SiO 2 materials. 12 Reber et al 28 demonstrated that SiO units assemble to form bigger clusters, with silicon rich agglomerations at the center and oxygen rich structures at the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…The second is the "nanochain" morphology, wherein beads of Si nanocrystals passivated by a thin surface oxide are connected by fine amorphous silica nanowires to other Si nanocrystals, much like a string-of-pearls. While VS growth models for nanowire formation have been proposed [35], the mechanism for nanochain formation remains poorly studied; one speculation is that impurity incorporation at the beads plays an important role [36]. Both types of Si nanostructures are seen in the TEM micrograph in Fig.…”
Section: Morphologiesmentioning
confidence: 97%
“…The phenomenon of {111} twinning in Si nanowires, prepared using a method similar to ours, has already been studied closely in the literature [44]. The high incidence of twinning in Si nanowires appears to be unique to the "oxideassisted" VS-growth system [35], since Si nanowires prepared using VLS catalyzed chemical vapor deposition (CVD) do not appear to contain these defects [11,45]. Oxygen in the growth system may be responsible, since it is known that Czochralski-grown Si is vulnerable to oxygen-induced stacking faults [46].…”
Section: Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen plays an important role in nucleation and growth of nanowires. The OAG technique allows large quantities of pure nanowires to be produced [13]. …”
Section: Nanowires (Nw)mentioning
confidence: 99%